Exploring the Multidimensional Assessment of Interoceptive Awareness in youth aged 7–17 years. Issue 3 (9th October 2020) - Jones, Alexander; Silas, Jonathan; Todd, Jennifer; Stewart, Anita; Acree, Michael; Coulson, Mark; Mehling, Wolf E.
Abstract: Objective: This study aimed to adapt the Multidimensional Assessment of Interoceptive Awareness (MAIA) questionnaire for younger respondents. Method: The language of the MAIA was revised and children aged 7–10 years ( n  = 212) and adolescents aged 11–17 years ( n  = 217) completed the questionnaire. Results: The original eight‐factor model was tested for fit using confirmatory factor analysis. The model had an acceptable fit in the total sample and younger subsample and overall fit in the older subsample was adequate following modification. Internal consistency was good, except for the Noticing, Not‐Distracting and Not‐Worrying scales. Results also demonstrated a negative linear relationship between the trusting scale and age, suggesting that youths may lose trust in their body as they age. Conclusion: The adapted MAIA can be used with a younger population and, depending on the research question, individual MAIA scales may be selected. The survey is available at https://osher.ucsf.edu/maia .